Audiologic results of a child with BVVL syndrome (Annals of Medical Research, 2023)
Brown-Vialetto-Van Laere (BVVL) syndrome is an autosomal-recessive inherited disease, which has mutations in specific genes responsible for the transportation of riboflavin in the intestines. Fifty-eight cases of BVVL have been reported in just over a century. This rare syndrome is generally characterized by motor, sensory, and cranial nerve neuropathy. Although this syndrome manifests with bulbar palsy, sensorineural hearing loss is the second most common consistent manifestation of BVVL syndrome. While auditory neuropathy spectrum disorder (ANSD) often awaits due to the nature of the disease here, we present the results of cochlear hearing loss patient with BVVL syndrome. Timely recognition and proper management of BVVLS are crucial to offer necessary support and interventions for affected individuals because of the progressive nature of hearing loss.
Keywords: Brown-Vialetto-Van Laere syndrome; Sensorineural hearing loss; Auditory brainstem response; Congenital hearing loss